Pengaruh Lingkungan Kerja, Komunikasi, Kompetensi, dan Motivasi Terhadap Kinerja Pengurus ( Studi Kasus Pada PK IPNU IPPNU UNISMA ) - Ramadhan, Reza Rahmad; Widarko, Agus; Primanto, Alfian Budi (UNIVERSITAS ISLAM MALANG, 2024)
AbstractÂ This research aims to analyze the ifluence of work environment, communication, competence, and motivation on the performance of PK IPNU IPPNU UNISMA. The research was conducted using a survey method of 86 respondents using saturated sampling technique. The data analysis method used in this research was quantitative data analysis using multiple linear regression analysis. The data test used is partial hypothesis testing (t test). The research results show that the work environment, competence, and motivation have a significant effect on management performance, while communication does not have a signicant effect. In conclusion, comfort in the work environment and high competence can improve management perfomance the higher the motivation, the lower the management performance, but good communication does not have a significant effect on management performance.Â Keywords: Work Environment, Communication, Competence, Motivation, And Management Performance.Â